2017
DOI: 10.1016/j.amjcard.2016.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Practices of Women With Complex Congenital Heart Disease

Abstract: Understanding the contraceptive practices of women with complex congenital heart disease (CHD) and providing them individualized contraception counseling may prevent adverse events and unplanned high-risk pregnancies. Given this, we sought to examine the contraceptive practices in women with CHD, describe adverse events associated with contraceptive use, and describe the provision of contraception counseling. Women >18 years were recruited from 2011 to 2014 from 9 adult CHD (ACHD) centers throughout North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
4
24
1
Order By: Relevance
“…19,20 One of these studies found a higher percent of thromboembolic conditions in women with more severe CHD compared with mild CHD. Two of three comparative studies found a higher percent of thromboembolic complications among women with Fontan palliation or transposition of the great arteries using oral contraceptives than among women not using oral contraceptives; however, statistical testing was not reported for these comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19,20 One of these studies found a higher percent of thromboembolic conditions in women with more severe CHD compared with mild CHD. Two of three comparative studies found a higher percent of thromboembolic complications among women with Fontan palliation or transposition of the great arteries using oral contraceptives than among women not using oral contraceptives; however, statistical testing was not reported for these comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…4 Two studies found no endocarditis among IUD users. 19,20 Two studies did not report outcomes by specific type of contraception, but rather grouped all methods together. All studies were rated as poor quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations